Description of Malenchus gilanensis n. sp. from Iran - Jalalinasab, Parisa; Adeldoost, Yaser; Abolafia, Joaquín; Heydari, Ramin (Zootaxa, 2019)
Malenchus gilanensis n. sp. is described and illustrated from wood samples from Iran. Morphologically, this new species is characterized by very small body size, cuticle with narrow annuli (0.8–0.9 μm wide at mid-body), lateral field with two lines, originating at the level of the median pharyngeal bulb valve, straight amphidial apertures (similar to members of the subgenus Telomalenchus), sunken vulva with large lateral flaps, prophasmids located almost level with to 9 annuli posterior to the vulva in females, and undeveloped adanal bursa which can be considered as an outgrowth of the lateral field in males. Malenchus gilanensis n. sp. resembles members of subgenus Telomalenchus due to the straight amphidial apertures, prophasmid position and large lateral flaps, but it differs by having two lines in the lateral fields. This new species is morphologically similar to five known species of the subgenus Malenchus: M. acarayensis, M. bryanti, M. parvus, M. nanellus and M. truncatus. The new species can be distinguished from them and other species in the subgenus by having straight amphidial apertures, two lines in the lateral fields, position of prophasmids, and having a very small and undeveloped bursa.